Cost-effectiveness of iruplinalkib versus crizotinib in first-line anaplastic lymphoma kinase-positive advanced non-small-cell lung cancer patients in China - Zhang, Wanjie; Lu, Yuqiong; Dai, Zhanjing; Wang, Linning; Zhou, Yang; Lu, Yun; Chang, Feng (Frontiers in Pharmacology, 2025)
BackgroundThe recently completed INSPIRE trial demonstrated that iruplinalkib improved progression-free survival and intracranial antitumor activity compared with crizotinib in patients with anaplastic lymphoma kinase (ALK) -positive non-small-cell lung cancer (NSCLC). The objective of this study was to determine the potential cost-effectiveness of iruplinalkib vs. crizotinib in the Chinese healthcare setting.MethodsA cost-effectiveness model was developed using the partition survival method, with three health states: progression-free survival, progressive disease, and death. Data from the INSPIRE trial were used to estimate progression-free and overall survival. Costs included drug treatment, disease management, and adverse events management. Drug costs and utilities were the main drivers of the model in the deterministic sensitivity analysis.ResultsTreatment with iruplinalkib versus crizotinib resulted in a gain of 0.55 life-years, 2.11 quality-adjusted life-years (QALYs), and an incremental cost of 4,325.55, resulting in an incremental cost-effectiveness ratio of 2,048.03/QALY. Drug costs and utilities were the main drivers of the model in the deterministic sensitivity analysis. From the probabilistic sensitivity analysis (PSA), iruplinalkib had a 100% probability of being cost-effective at a willingness-to-pay threshold of 13,447.89/QALY.ConclusionCompared to crizotinib, iruplinalkib is a cost-effective therapy for treatment-naïve patients with ALK-positive NSCLC.